Effects of mannan level and β-mannanase supplementation on growth performance, apparent total tract digestibility and blood metabolites of growing pigs - J.S. Kim; S.L. Ingale; A.R. Hosseindoust; S.H. Lee; J.H. Lee; B.J. Chae (Animal, 2017)
The exogenous enzymes are less consistent in their effects as their beneficial effects depend upon the types and level non-starch polysaccharides (NSP) present in the diets. Therefore, exogenous enzymes should be selected on the basis of types and amount of the NSP in the pig diets. The objectives of the present experiments were to investigate the effects of dietary level of mannan and β-mannanase supplementation on growth performance, apparent total tract digestibility (ATTD) of energy and nutrients, and blood metabolites of growing pigs. In Exp. 1, 96 barrows were randomly allotted to four treatments on the basis of BW. There were four replicates in each treatment with six pigs per replicate. The dietary treatments were a corn–soybean meal (SBM)-based control diet and three other diets consisted of the control diet supplemented with 400, 800 or 1600 U of β-mannanase/kg diet. The final BW, average daily gain (ADG) and blood glucose increased (linear, P<0.05) with increasing concentrations of dietary β-mannanase. The ATTD of dry matter (DM), gross energy (GE) and β-mannan was higher (linear, P<0.05) with increase in dietary β-mannanase concentrations. In Exp. 2, 288 barrows were allotted to six treatments in a 2×3 factorial arrangement of mannan level (high v. low) and addition of β-mannanase (0, 400 or 800 U/kg diet). There were four replicates in each treatment with 12 pigs/replicate. Pigs were fed corn–SBM-based low-mannan diet (6.1 g/kg) or high-mannan (25.2 g/kg) diet in which corn and SBM were partially replaced with 50 g/kg diet palm kernel meal. All diets were fed in meal form for 42 days. Pigs fed diets supplemented with β-mannanase had greater (P<0.05) final BW, ADG, feed to gain (F : G), the ATTD of DM, GE, and β-mannan and blood glucose concentration compared with pigs fed diets without β-mannanase. In addition, the final BW, ADG, F : G and the ATTD of GE and β-mannan were reduced (P<0.05) in low mannan level. The dietary level of mannan and the β-mannanase supplementation had no effects (P>0.05) on the concentrations of blood total cholesterol, triacylglycerides and blood urea nitrogen. These results indicate that supplementation of β-mannanase to low- or high-mannan diets have potential to improve the performance of growing pigs. In addition, palm kernel meal may partially replace corn and SBM without reducing pig performance if β-mannanase is added to diet.